Nilai-Nilai Sosiologi Yang Terkandung Dalam Ajaran Agama Islam - Hidayah, Nur; Nelly (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2024)
Sociology is a discipline that includes certain subjects, methodologies, and approaches used to explore and gain new knowledge. In the study of the sociology of religion, the focus is on the religious community as a space that includes the study, emphasizing social phenomena in a society that practices religion rather than the teachings of religion itself. From a sociological perspective, religion is seen as a way of life that must be practiced in society, which encourages relationships between individuals. Furthermore, religion plays an important role in shaping the social structure of society. A sociological approach is important to reveal the nature of religion, because the study of religion presents a complexity that can be studied carefully through a sociological perspective. This study is important to explain the sociological approach in the study of Islam. By gaining a comprehensive understanding of sociological values ​​in the study of Islam, including the scope and issues that exist. This study uses a qualitative approach, especially by using the library research method. The discussion method in this study uses a descriptive analytical approach, which aims to provide explanations and connect key ideas or concepts related to the topic being studied. In Islamic teachings, it is stated that for every verse related to worship, there are one hundred verses about muamalah (social problems). The importance of muamalah or social issues in Islam is emphasized by the fact that when the time of worship coincides with important social affairs. It can be seen that the Islamic religion always prioritizes the interests of social values ​​rather than individuals. This proves that Islamic teachings highly uphold sociological values.